MODIFICATION OF SURFACE MESH FOR THE GENERATION OF KNIFE ELEMENT FREE HEXAHEDRAL MESH (Journal of Mechanical Engineering, 2011)
Hexahedral elements provide greater accuracy and efficiency over tetrahedral elements for finite element analysis of solids and for this reason the all-hexahedral element auto meshing has a growing demand. The whisker-weaving based plastering algorithm developed by the authors can generate hexahedral mesh (HM) automatically. In this method the prerequisite for generating HM is quadrilateral surface mesh (SM). From the given SM, combinatorial dual cycles or whisker sheet loops for whisker weaving algorithm are generated to produce HM. Generation of good quality HM does not depend only on the quality of quadrilaterals of the SM but also on the quality of the dual cycles generated from it. If the dual cycles have self-intersection, it could cause the formation of degenerated hexahedron called knife element, which is not usable in finite element analysis. In this paper a detailed method is proposed to modify the SM to remove self-intersections from its dual loops. The SM modification procedure of this proposed method has three basic steps. These steps are (a) face collapsing, (b) new face generation and (c) template application. A fully automatic computer program is developed on the basis of this proposed method and a number of models are analyzed to show the effectiveness of the proposal.DOI: http://dx.doi.org/10.3329/jme.v41i2.7505